Pembacaan Rotibul Haddad sebagai Sarana Dakwah Nahdlatul Ulama di Desa Sedah, Ponorogo - Fauza Ni'amatul Mubarokah; Akhmad Rifa'i (UIN Raden Mas Said Surakarta, 2023)
Rotibul haddad is one of the da'wah activities in the form of practicing dhikr with various fadhilah in it. People tend to practice rotibul haddad in the congregation rather than practicing it privately. This study aims to explain why the people of Sedah Village, Ponorogo, prefer to perform the rotibul haddad remembrance in congregation in routine activities initiated by three banom of Nahdlatul Ulama. The research used a qualitative approach with descriptive data analysis from the results of interviews and observations. This study found that the implementation of routine rotibul haddad dhikr activities carried out together, are more favored by the people of Sedah Village, Ponorogo. Zikr rotibul haddad done alone feels difficult and boring, plus the daily routine, as well as the lack of rotibul haddad book references. The people of Sedah Village, Ponorogo, feel the positive impact of this routine activity and are more interested in practicing the zikr of rotibul haddad because of many fadhilah.